2017
DOI: 10.1007/s40094-016-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Self-focusing of a high-intensity laser pulse by a magnetized plasma lens in sub-relativistic regime

Abstract: Interaction of high power circularly polarized short laser pulses with a cold underdense magnetized thin plasma lens is analyzed in the sub-relativistic regime. The magnetic field is applied along the direction of the laser field propagation. The evolution equation of the beam spot size is derived and solved by making use of the variational principle approach method. The theoretical investigations reveal that not only the magnetized plasma lens more sufficiently decreases the laser spot size, but also the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, high‐intensity laser pulses can propagate only up to the relativistic cutoff density into unmagnetized inhomogeneous plasma. It is well known that intense magnetic fields are generated in the laser plasma interaction and the propagation of high‐intensity laser pulses in plasma is strongly affected by the presence of magnetic fields . There have been limited studies of self‐focusing of intense laser beams in magnetized plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high‐intensity laser pulses can propagate only up to the relativistic cutoff density into unmagnetized inhomogeneous plasma. It is well known that intense magnetic fields are generated in the laser plasma interaction and the propagation of high‐intensity laser pulses in plasma is strongly affected by the presence of magnetic fields . There have been limited studies of self‐focusing of intense laser beams in magnetized plasma.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that self‐focusing property of the laser beam enhances in the presence of external magnetic field. Abari et al have recently studied the self‐focusing of a high‐intensity laser pulse by a magnetized plasma lens in a subrelativistic regime. They concluded that the magnetized plasma lens more sufficiently decreases the laser spot size and the left‐handed circularly polarized beam is more effectively focused by a magnetized plasma lens compared to the right‐handed circularly polarized beam.…”
Section: Introductionmentioning
confidence: 99%